SYNERGY OF SHARIA BANKS AND FINANCIAL TECHNOLOGY IN THE DEVELOPMENT OF MICRO, SMALL AND MEDIUM BUSINESSES IN INDONESIA - Haris, Muhammad; Iqbal, Muhammad; Hadiyati, Puji (Jurnal Reviu Akuntansi dan Keuangan)
ABSTRACTThe purpose of this study is to analyze the synergy between sharia bank and fintech to effort and develop micro, small and medium enterprises (MSMEs) in Indonesia. Data and information were obtained through interview to expert respondents in their fields such as BNI Syariah, Ammana Fintek Syariah and the Otoritas Jasa Keuangan (OJK). This study has been conducted from July 2018 to March 2019. To provide a deep understanding, this study uses a qualitative approach. The results of the study to show that the opportunity to create synergy between Sharia Bank and Sharia Fintech in order to develop MSMEs in Indonesia is still very wide open. This synergy can be done through several existing patterns or synergy models, including through cross-selling schemes, channeling, references, shadow investors, outsourcing platform and Fintech consortium. The benefits of this synergy include empowering MSMEs, facilitating financial services that are practical, comfortable, safe, have speed, sophistication and up-to-date and are more efficient. The challenges ahead are in terms of human resources competence and support from regulators for policy relaxation. Risks that must be properly mitigated from these synergies, such as the risk of credibility, technology, default and operations.KEYWORDS:Â Financial Technology (Fintech); Micro; Small and Medium Enterprises; Sharia Bank, Synergy.